A conformal cavity-backed supergain slot antenna - Chen, Zhuozhu (2014)
A conformal supergain slot antenna is presented in this paper, which comprises a thin substrate on the top broad wall of a shallow metallic cavity. Three slots with different lengths are etched out at suitable positions of the cavity wall to enhance the bandwidth as well as to achieve the supergain. A large ground is employed to obtain the near-end-fire radiation pattern. The proposed conformal antenna operates at the center frequency of 10 GHz. Simulated results show that a fractional bandwidth of 15% and maximum gain of 9.1 dB can be obtained for the three-slot conformal structure, the maximum radiation pattern tilts from the end-fire direction. A prototype of the proposed antenna is fabricated and tested. Measured results are in good agreement with simulated ones.